{Hydrology and circulation in the Southern Cretan Sea during the CINCS experiment (May 1994–September 1995)} - Georgopoulos, D; Chronis, G.; Zervakis, V; Lykousis, V.; Poulos, S.; Iona, A (Progress in Oceanography, 2000)
This work is a description of the water masses and circulation in the site of the CINCS (Pelagic–Benthic Coupling IN the Oligotrophic Cretan Sea) experiment in the southern boundary of the Cretan Sea, a region of recently renewed interest with respect to the hydrology of the Eastern Mediterranean Basin. Analysis of hydrological data from the study area reveals the presence of five water masses: local surface water and remotely advected Modified Atlantic Water (MAW) share the surface layers below them are Cretan Intermediate Water (CIW), between 50 and 150 dbar, Transition Mediterranean Waters (TMW) with its core located between 300–400 dbar, and the Cretan Deep Waters (CDW) occupying the depths below 800 dbar. The circulation over the coastal shelf and slope is dictated by the offshore semi-permanent mesoscale features that dominated the Cretan Sea in 1994–1995, forcing locally a shoreward flow. The hydrographic observations are verified by current-meter measurements from a mooring in the sampling area. The recorded velocity is generally towards the SE direction, seasonally modulated, reaching maximum speeds of 27 cm s−1. Analysis of the new data set has revealed a previously unobserved feature of the oceanographic characteristics of the region. Over the base of the Cretan Slope there occur lenses of water that are warmer and more saline than their surroundings. These lenses probably form on the shelf seasonally; their waters are rich in oxygen, and have a density that is higher than historical Cretan Deep Water values.